Analisis Penggunaan Indeks Literasi Zakat pada Petani Terhadap Zakat Pertanian di Kabupaten Kerinci Provinsi Jambi - Muhammad Shodiqin; Titin Agustin Nengsih; Iqbal Bafadhal (Universitas Batanghari Jambi, 2026)
This research is motivated by the zakat on rice farming in Kerinci Regency which has not been managed optimally. This research aims to determine the literacy level of farmers regarding agricultural zakat in Kerinci Regency using the Zakat Literacy Index, to determine the understanding variables that are obstacles in farmer literacy towards agricultural zakat in Kerinci Regency, and to understand the patterns and behavior of farmers regarding the payment of agricultural zakat in the Regency. Kerinci. This research is quantitative research using primary data. The sample was selected by purposive sampling of 100 respondents and then analyzed using the Zakat Literacy Index method. The results of this research are that the literacy level of rice farmers regarding agricultural zakat in Kerinci Regency obtained a score of 60.74, which is in the middle/moderate category. Then the variables that are obstacles in rice farmers' literacy towards zakat in Kerinci Regency are; knowledge variable about zakat objects in the basic dimension as well as knowledge variables about zakat institutions), knowledge about zakat regulations, knowledge about zakat distribution programs, and knowledge about digital zakat payments in the advanced dimension. The patterns and behavior of rice farmers in Kerinci Regency are; Ownership of dominantly owned land with a percentage of 76%, land area under dominant cultivation